2018
DOI: 10.22159/ajpcr.2018.v11i9.26831
|View full text |Cite
|
Sign up to set email alerts
|

Study of in Vivo Pharmacokinetic Drug Interactions of Curcumin on Tacrine

Abstract: Objective: Tacrine is a potent acetylcholine esterase inhibitor (AChEI), and curcumin has been recently proven to possess AChEI, amyloid β aggregation inhibitory activity in addition to its diverse pharmacodynamic nature. Tacrine undergoes biological transformation by cytochrome P450 (CYP 1A2) to a hydroxy metabolite, which is hepatotoxic. Curcumin is known for its inhibitory nature for various metabolic enzymes along with CYP1A2. The present study was undertaken to evaluate the influence of curcumin on the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A recent study also showed that CM administered together with TMX increased the anticancer activity, as compared with TMX alone. This effect may occur through the suppression of P-glycoprotein (MDR1) expression [16][17][18]. Squirewell et al [14] proposed a mechanism of the interactions of polyphenols, including CM, with ABC transporters and showed that polyphenols counteracted tumor cell chemoresistance by interacting with the ATP-binding domains of P-glycoprotein and inhibits its ATPase activity site and steroid interacting regions of the protein cytosolic domains [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that CM administered together with TMX increased the anticancer activity, as compared with TMX alone. This effect may occur through the suppression of P-glycoprotein (MDR1) expression [16][17][18]. Squirewell et al [14] proposed a mechanism of the interactions of polyphenols, including CM, with ABC transporters and showed that polyphenols counteracted tumor cell chemoresistance by interacting with the ATP-binding domains of P-glycoprotein and inhibits its ATPase activity site and steroid interacting regions of the protein cytosolic domains [13].…”
Section: Discussionmentioning
confidence: 99%